Authority of a Notary in Legalizing the Establishment of a Limited Liability Company After the Job Creation Law Was Passed - Saputra, Muhammad Rezki Wira; Hafidz, Jawade (Jurnal Konstatering, 2023)
The legal basis for Limited Liability Companies in Indonesia has changed with the enactment of Law No. 6 of 2023 concerning Job Creation which replaced Law No. 40 of 2007. Capital partnership businesses and limited liability companies are now two parts of limited liability companies. As a result of these changes, this research aims to examine the authority of notaries in validating the establishment of limited liability companies after the ratification of Law No. 6 of 2023 concerning Job Creation. This research uses a normative juridical approach method through literature study techniques. Based on research findings, the presence of a notary is still needed when a company must change its legal status to a capital partnership company after the Job Creation Law is passed. This situation arises if the number of shareholders exceeds one person and/or the company no longer meets the criteria as a Micro and Small Enterprise. Before an individual company can change its status to a capital partnership company, this status transition must be carried out through a notarial deed and then registered electronically with the Minister.